Understanding Group Energy in University Language Classes - Pohl, Uwe; Szesztay, Margit (Working Papers in Language Pedagogy, 2010)
In this paper two university language tutors explore the notion of group energy as a key factor in the dynamics of their language classes. In particular, the article focuses on the way teacher presence impacts on the quality and level of energy in classroom groups. The findings, primarily based on interviews with experienced colleagues, suggest that teachers have preferred ways of accessing and aligning the flow of energy in a given group. The authors identify a number of such access points to group energy as well as their different manifestations.